Cybersecurity Decision-Making in the C-Suite: A Framework for Managerial Engagement - Thapaliya, Suman; Panta, Sangita (Journal of Engineering Issues and Solutions, 2025)
In an era of escalating cyber threats and digital transformation, cybersecurity has emerged as a critical concern for organizational leadership. This study explores the evolving role of C-suite executives in cybersecurity governance and decision-making, addressing the disconnect between technical operations and strategic oversight. Through a qualitative, multi-case study approach involving in-depth interviews with senior executives across various sectors, the research identifies key gaps in awareness, engagement, and cross-functional communication. The findings reveal that while executives increasingly acknowledge cybersecurity as a strategic risk, their active participation remains limited due to a lack of cyber literacy, role ambiguity, and insufficient governance structures.To bridge this gap, the study proposes the Cybersecurity Managerial Engagement Framework (CMEF)—a practical model comprising four key pillars: Leadership & Culture, Strategic Alignment, Governance & Oversight, and Resource Allocation & Communication. The framework aims to enhance executive-level involvement in cybersecurity by promoting informed decision- making, cross-functional collaboration, and alignment with business objectives. The research contributes to both theory and practice by emphasizing that cybersecurity is not just a technical imperative but a leadership responsibility essential for organizational resilience and long-term success.